Interpretation of the horizontal beam response near the third integer resonance - Cortés García, Edgar Cristopher; Niedermayer, P.; Singh, R.; Taylor, R.; Feldmeier, Eike; Hun, Marcel; Benedetto, E.; Haberer, Thomas (Physical review accelerators and beams, 2024)
The beam response to an external periodic excitation delivers relevant information about the optics, tune distribution, and stability of a circulating beam in a storage ring. In this contribution, the horizontal beam response to the excitation (transfer function) under conditions typical for slow extraction is presented for a coasting beam. The resulting spectrum exhibits a splitting behavior. The single particle dynamics is discussed and an interpretation based on the simulation results is presented.
Gesehen am 05.12.2025